The Effectiveness of Brain Gym and Brain Training Intervention on Working Memory Performance of Student with Learning Disability - Bungawali Abduh; Mohd Mokhtar Tahar (Journal of ICSAR, 2018)
Learning disability is commonly associated with a weak working memory function of a student that impacts his or her performance in school. This study aims to identify the effective approaches that could enhance the working memory function of students with learning disability. This quasi-experimental study involved three group of five students that were allocated into control group, Brain Gym, and Brain Training intervention group. The Brain Gym intervention group performed Brain Gym ® Superspace exercise on a daily basis for four weeks during the first school session. Meanwhile, Brain Training intervention was carried out by another intervention groups on a daily basis for four weeks. They were allocated with 5-minutes Brain Training game for each person in a group during free time at school. Data for the working memory function that were collected during pre- and post-test using three instruments: (1) Digit Span  Memory Test; (2) Spatial Memory Test; and (3) Picture Identification Test.  Two non-parametric test was used to interpret the data: (1) Spearman Rank Order Correlation to determine the relationship of the three groups on the pre- and post-test and Wilcoxon Pair Signed Rank Test to measure the difference between pre- and post-test scores for the control group, two intervention groups, and three working memory component. The findings of the study show a significant increment of the working memory function for both intervention groups. The finding also shows a significant increment for Digit Span Memory and Spatial Memory skills among participants in the intervention group. This study provides alternative to parents, teachers and school administration to provide appropriate learning stimulus that could fulfill the needs of students in school and at home.